Analyze of early childhood education in the context of inclusive education - Prudnikova, Ilga; Jankovska, Jekaterina (Social Welfare: Interdisciplinary Approach, 2015)
Early childhood education means a sequence of levels of education, where the foundation is the concept of "early childhood.” Early childhood is a foundation for social skills knowledge and advances on the following level of education. The imposition of necessary support measures in the education and care of pre-school process provides successive children with special needs inclusion in next level of education. Qualitative early childhood education and care system development principle is that of making early childhood education available for appropriate needs of children and family. The article main tasks is analyze about statistic of early childhood available, analysis of the theories of early development and early child with special needs inclusion education.